Konseling Ekologi Bronfenbrenner dalam Pengembangan Kecerdasan Spiritual Sebagai Fitrah Anak (Spiritual Intelligence) - Muhyatun, Muhyatun (Jurusan Bimbingan dan Konseling Islam, 2019)
The biggest challenge in the current global era is internalizing the values of honesty, tawadhu values and ta'awun values for children as the essence of the development of spiritual intelligence. This condition is reinforced by the emergence of behavioral phenomena of children who like to lie, fight and commit acts of violence against parents, teachers or other people. This certainly contradicts the values contained in the essence of spiritual intelligence that every child should have. So from that it takes the right effort in overcoming this. The purpose of this study is to find out the efforts that can be used in developing children's spiritual intelligence contained in the concept of ecological counseling. The study method used is the study of literature. The results of the study carried out stated that there were several efforts that could be used in developing children's spiritual intelligence, namely the development of children's spiritual intelligence in the microsystem environment, the first and most important environment in a child's development, including the development of spiritual intelligence